Student Difficulties in Addition and Subtraction of Two Digit Numbers - Mauhibah, Rohma; Karso, Karso (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Two digits addition and subtraction are important ability that must be mastered by all of student in elementary school. Because this skill will be the pre condition for further activities in mathematics. But, there are some student still have difficulties on it. This study describes about the student difficulties in solving addition and subtraction problem. The respondent are 28 student of second grade in SDN 033 Asmi Bandung. Research instrument is written test. There are three purpose of question (1) To know student ability on solving direct addition and subtraction problem, (2) To know student understanding on the meaning of operation. and (3) To know student understanding on relationship between addition and subtraction. There are three part of question. According to the findings obtained from the test, the students had some difficulties. The most difficulties is 78% of participant fail to answer 46 – 28= … . They can not do subtraction which is need to borrow. It is indicate that they just do the procedure without understanding the consept of operation. And then in question (… - 7 = 9 + 15 = …) there was 50% of student can not solve the problem. It indicate that they dodn’t understand on relationship between addition and subtraction